Parenting Education sebagai Model Pendidikan Karakter Anak Usia Dini Berbasis Keluarga - Rohinah, Rohinah (Program Studi Pendidikan Guru Raudlatul Athfal, UIN Sunan Kalijaga Yogyakarta, 2016)
Character education is an effort that should involve all parties, both the household and the family, the school and the school environment, and the wider community. A child will grow and develop optimally when the basic needs of the children's rights are met. But in reality often violent behavior and discrimination that actually carried out by her own parents. Violent behavior and racial discrimination by parents of children often occurs due to the psychological impact of the workload and the demands of a career outside the home or it could be due to a lack of knowledge about how to educate and assist children in the home. Hence, early childhood institutions